Word and meaning consideration of tongue pests in Masnavi Manavi of Molavi and religious knowledge regeneration of Ghazali - Mohammad Sadegh Basiri; somayeh hoseyni (ادبیات تطبیقی, 2016)
Different ways exist to express purposes. Some select the direct way, which means they prefer formal and non-literary language, in this way sentences would be predicative. But some others select in direct language because they believe it is more effective. Of importance and noticeable subjects are pests and sins of tongue. The reason is more than benefits and value of tongue and express its sins and pests are Harmful and undesirable, and same as there is no devoutness better than rightful speak, there is no sin worse than Speaking unjustly to god. There are lots of valuable subjects and words in divine teachings and wises words about tongue pests which we cannot speak about all but will consider some of them from religious knowledge regeneration by Ghazali and from Manavi Manavi by Molana. In this article we are about to clarify that how Imam Mohammad Ghazali and Molavi sent their message to the readers and which way they have chosen (direct or indirect). And how is their way of express from the aspect of word and meaning